Beliefs, knowledge and attitudes towards Parkinson's disease among a Xhosa speaking black population in South Africa: A cross-sectional study. (August 2017) - Mokaya, Jolynne; Gray, William K.; Carr, Jonathan
Abstract: Introduction: Many patients with Parkinson's disease (PD) in sub-Saharan Africa (SSA) are thought to be undiagnosed and untreated, leading to poor health outcomes. Increasing rates of diagnosis and treatment, with consequent improvements in the quality of life of people with PD in SSA requires an understanding of how PD is perceived and conceptualized within communities. Methods: A cross-sectional survey was conducted among a group of Xhosa speaking black South Africans. The survey involved the administration of questionnaires on beliefs, knowledge and attitudes about PD to the public, people with PD (PwPD) and traditional healers (THs). Results: 18% of the participants could identify PD through its symptoms. Mental illness, other diseases, stress, expressing strong emotions, consumption of certain foods or drinks and witchcraft were identified as possible causes of PD. PwPD and THs had a greater knowledge of PD than the public and greater age was a significant predictor of greater knowledge. The public and THs had a greater degree of concern about a range of symptoms of PD compared to PwPD. Conclusion: There is a striking lack of knowledge about PD amongst black South Africans. Almost half the members of the general public interviewed felt that PwPD should not live amongst their community, and a third considered that witchcraft could be a cause of PD. Finding ways to effectively educate members of a community about PD would make it easier for PwPD to adapt to their condition within their communities. Highlights: There is a striking lack of knowledge about PD in our background population. Many considered witchcraft a cause of PD. PD awareness campaigns may help to increase knowledge and reduce stigma.